The Effect of Current Ratio and Working Capital Turnover on Net Profit Margin in Transportation and Logistics Companies Listed on the Indonesia Stock Exchange for the 2018-2024 Period - Cristine Prestarika Lukito; Hasanudin (Cita konsultindo, 2026)
This study aims to determine the effect of the current ratio and working capital turnover on the net profit margin of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange for the period 2018–2024. The research method used is quantitative. The sample in this study consists of 48 observations. Data analysis techniques include classical assumption tests, multiple regression, and hypothesis testing using EViews 12 software. The results show that, when analyzed partially, the Current Ratio does not have a significant effect on the Net Profit Margin, with a t-calculated value < t-table (0.105003 < 2.004) and a significance level of 0.9168 < 0.05. Therefore, H01 is accepted and Ha1 is rejected. Working Capital Turnover, when analyzed partially, does not have a significant effect on the Net Profit Margin, with a calculated t-value < table t-value (0.250980 < 2.004) and a significance level of 0.8029 > 0.05; therefore, H02 is accepted and Ha2 is rejected. The results of the F-test indicate that the Current Ratio and Working Capital Turnover simultaneously have a significant effect on the Net Profit Margin, with the calculated F-value > the table F-value (5.225155 > 3.16) and a significance level of 0.000064 < 0.05. Therefore, Ha1 is accepted and H0 is rejected. With a coefficient of determination of 41.10%, the remaining 58.90% is influenced by other factors.